(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
The problems of digitalisation and transition of companies into the digital markets has become one of the crucial issues in contemporary business. Digital transformation is changing markets and interactions. These trends impose a question on how secure is this environment and how companies are combating this issue. This new environment shows us how knowledge is dispersed across a global market and in individual, national, markets. The goal of the research is to investigate the differences between countries in Europe according to how their companies tackled the challenges of IT security. Clustering is conducted by the use of simple k-means method using the data on European countries available in Eurostat. The digital divide has been found among European countries according to their usage of investigated IT security practices. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.